2017
DOI: 10.1002/jor.23768
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling of in situ chondrocytes in articular cartilage under compressive loading: Roles of calcium sources and cell membrane ion channels

Abstract: Mechanical loading on articular cartilage can induce many physical and chemical stimuli on chondrocytes residing in the extracellular matrix (ECM). Intracellular calcium ([Ca ] ) signaling is among the earliest responses of chondrocytes to physical stimuli, but the [Ca ] signaling of in situ chondrocytes in loaded cartilage is not fully understood due to the technical challenges in [Ca ] imaging of chondrocytes in a deforming ECM. This study developed a novel bi-directional microscopy loading device that enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 44 publications
3
52
0
Order By: Relevance
“…These pathways can be grouped into 3 categories: extracellular Ca 2+ source, intracellular Ca 2+ store, and Ca 2+ ion channels on the plasma membrane. Several studies concluded that the stimulated calcium signaling in chondrocytes required an extracellular Ca 2+ source (13, 14). Previously, we also found that no calcium signaling can be initiated in osteocytes or osteoblasts when placing the cells in Ca 2+ ‐free medium.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways can be grouped into 3 categories: extracellular Ca 2+ source, intracellular Ca 2+ store, and Ca 2+ ion channels on the plasma membrane. Several studies concluded that the stimulated calcium signaling in chondrocytes required an extracellular Ca 2+ source (13, 14). Previously, we also found that no calcium signaling can be initiated in osteocytes or osteoblasts when placing the cells in Ca 2+ ‐free medium.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the MAPK signaling pathway has been found to receive, transduce and convey mechanical information to the chondrocyte interior [37], which also evidenced by the enrichment of negative regulation of stress-activated MAPK cascade in the overlapped genes. Intracellular calcium signaling is among the earliest responses of chondrocytes to physical stimuli and plays an important role in the mechanobiology of chondrocytes in a natural residing environment [38]. Here, calcium ion binding was also found to be the significant enrichment for the DEGs, which suggested the role of calcium ion channel and downstream pathway in the mechanical stress-induced osteoarthritic development.…”
Section: Discussionmentioning
confidence: 61%
“…A few studies have found [Ca 2+ ] responses under various mechanical stimulations . One of our previous studies utilized FLIPUS to induce Ca 2+ influx in vitro .…”
Section: Discussionmentioning
confidence: 99%